2009
DOI: 10.1021/jo9007628
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Hydride Reduction of an NAD+ Analogue by Isopropyl Alcohol in Aqueous and Acetonitrile Solutions: Solvent Effects, Deuterium Isotope Effects, and Mechanism

Abstract: The rate constants of the hydride-transfer reactions from isopropyl alcohol (i-PrOH) to an NAD(+) model, 9-phenylxanthylium ion (PhXn(+)), in acetonitrile (AN) and in water containing AN (80% H(2)O/20% AN) were determined over a temperature range from 36 to 67 degrees C. The reactions follow second-order rate laws. In the latter solution, formation of the water adduct of PhXn(+) was observed as a side-equilibrium (K). The observed inverse solvent kinetic isotope effect (k(H(2)O)(obs)/k(D(2)O)(obs) = 0.54), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…In order to further confirm the general hydride‐proton sequential transfer mechanism for this kind of hydride‐transfer reactions, KIEs at the α‐H(D), β‐CH 3 (CD 3 ), and OH(D) positions of the 1‐phenylethanol were determined by comparing the pseudo‐first‐order rate constants of the reactions of alcohols containing both isotopes under the same conditions. Values of primary KIE α‐D , secondary KIE β‐D3 , and secondary KIE OD are listed in Table 1, consistent with the corresponding KIEs observed for the 2‐propanol reaction in the same solvent (also listed in Table 1 for comparison)33 and indicating a stepwise mechanism (1) (see the subsequent discussion). Additionally, this research group is currently working on the study of temperature dependence of α‐D KIEs for some of the reactions studied in this paper, and has found that the KIE α‐D are all primary, further suggesting a rate‐limiting hydride transfer mechanism for this class of reactions.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…In order to further confirm the general hydride‐proton sequential transfer mechanism for this kind of hydride‐transfer reactions, KIEs at the α‐H(D), β‐CH 3 (CD 3 ), and OH(D) positions of the 1‐phenylethanol were determined by comparing the pseudo‐first‐order rate constants of the reactions of alcohols containing both isotopes under the same conditions. Values of primary KIE α‐D , secondary KIE β‐D3 , and secondary KIE OD are listed in Table 1, consistent with the corresponding KIEs observed for the 2‐propanol reaction in the same solvent (also listed in Table 1 for comparison)33 and indicating a stepwise mechanism (1) (see the subsequent discussion). Additionally, this research group is currently working on the study of temperature dependence of α‐D KIEs for some of the reactions studied in this paper, and has found that the KIE α‐D are all primary, further suggesting a rate‐limiting hydride transfer mechanism for this class of reactions.…”
Section: Resultssupporting
confidence: 81%
“…We have recently reported the kinetic and mechanistic study of the oxidation of 2‐propanol via hydride‐transfer to carbocationic oxidants (R + ) in various solvent systems to form the corresponding ketone product, the hydride reduction products of carbocations (RH) and a proton (Eqn (1), R 1 = R 2 = CH 3 ) 31–33. R + used include PhXn + and 10‐methylacridinium ion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26][27] Here, kinetics of the hydride-transfer reactions from alcohols to Xn + ClO 4 À in MeCN were similarly determined by following the decay of the Xn + UV-Vis absorption (Fig. S1, ESIw).…”
mentioning
confidence: 99%